Optimal Management during the Microorganism Culture Based on the Continuous Purifying Effort - Xianbin Wu (Discrete Dynamics in Nature and Society)
This paper deals with the problem of selective harvesting in a chemostat model. Here, we have taken the purifying effort as a dynamic variable and tax as a control instrument. The existence of the possible steady states along with their globally stable equilibrium is discussed. The optimal tax policy is also discussed with the help of Pontryagin's maximum principle. Finally, numerical examples are taken to illustrate some of the key results.